Fotocatálise heterogênea para tratamento de efluente gerado em uma lavanderia hospitalar de Telêmaco Borba-PR - Gomes, Rayne Azevedo (2023)
Pollution is directly or indirectly associated with industrial and domestic discharges the water undergoes physical, chemical and biological changes arising from this inappropriate discharge. Effluents originating from health services are places with pathogenic microorganisms and, considering the types of effluents from health units, those generated by hospital laundries present a potential risk to human health and the environment. The objective of this work was to analyze and treat with heterogeneous photocatalysis the effluents of a hospital laundry located in the city of Telêmaco Borba in the State of Paraná, applying three different types of catalysts in their treatment, namely, Titanium dioxide (TiO2), zinc (ZnAl2O4) and zinc aluminum impregnated with cobalt oxide (ZnAl2O4-Co3O4). The parameters pH, tubidity, conductivity, and coloration were compared before and after treatment. The pH parameter after treatment remained in accordance with CONAMA Resolution 357/2005, that is, between 6.0-9.0. The conductivity values after the treatment with the catalysts decreased, reaching the lower limit of the range stipulated by CONAMA resolution 357/2005. The turbidity before and after the treatment was within what is allowed by CONAMA resolution 357/2005, which is 100 NTU; however, there was a reduction after the catalysts acted, which is desirable since it is directly linked to the amount of organic matter suspended in solution. These results show that the TiO2 catalyst, widely used in effluent treatment processes, as well as the ZnAl2O4 and ZnAl2O4-Co3O4 catalysts, were effective in treating the effluent from a hospital laundry according to the studied parameters.